Economic Globalization: Encouraging Indonesian MSMEs to Become the Backbone of the National Economy - Nur Hikmah Zainal; Ainun Wildani; Andi Khusnul Khatima; Yasmin Syamsuddin; Fauzan Adipa (Public Resource Innovation Management and Excellence, 2025)
Economic globalization has opened markets and increased competition, but it also provides great opportunities for Indonesian MSMEs to thrive and become the backbone of the national economy. This study aims to analyze how MSMEs can take advantage of globalization to improve competitiveness, expand markets, and increase their contribution to the economy. The research method used is a case study with qualitative data analysis techniques through interviews and observations on MSMEs that have successfully penetrated the global market. The results show that successful MSMEs are those that are able to innovate, utilize technology, and build strong cooperation networks. In addition, support from the government and related institutions is also very important to create a conducive environment for the growth of MSMEs.